(untitled) (Research, Society and Development, 2022)
Introduction: In 2004, the Reception with Risk Classification (ACCR) began in Brazil for patients in in-hospital emergency care. By this way, pre-hospital care and screening of trauma victims considering mechanisms of injury and physiological criteria aimed at an adequate transport and a coherent destination for the patient under care. Objective: This study analyzed the screening of trauma victims rescued in the Econorte Concession, in the North region of Paraná-Brazil. Method: A bibliographic research was carried out in the database " PubMed” and a systematic qualitative and quantitative study of the Occurrence Reports filled in by the Concessionaire’s first responders and of the Compliance Control forms of the Concessionaire’s regulation center through a retrospective cohort survey in two periods: from January 1, 2015 to 31 from December 2016 and January 1, 2019 to December 31, 2020.Results: The description of the casualty’s profile, victims’ positions, accident location and under-triage and over-triage rates were obtained and presented in tables and graphs. Conclusion: The number of Occurrence Bulletins with adequate completion was higher in the second period and in them the risk classification of the victims was registered. sub-sorting in the two analyzed periods.